2019
DOI: 10.1108/ijebr-04-2018-0235
|View full text |Cite
|
Sign up to set email alerts
|

Shock Therapy and Entrepreneurial Flare #Brexit

Abstract: Much has been written about trade deal opportunities after Brexit (e.g. Minford et al, 2017; Singham & Tylecote, 2018) but much less about envisaged "supply side mechanisms" that would translate a Brexit shock into improved UK competitive performance. Indications as to the supply side mechanisms involved can be found in some pro Brexit writings and speeches and revolve around cutting regulation and reducing taxation, to spur innovation entrepreneurship. We contend that these measures align to a broad set of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Brexit is considered an event with economic, demographic and political drivers [30][31][32][33]. It is expected to have lower economic growth, lower foreign direct investment (FDI) and employment in the UK because of Brexit [33][34][35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brexit is considered an event with economic, demographic and political drivers [30][31][32][33]. It is expected to have lower economic growth, lower foreign direct investment (FDI) and employment in the UK because of Brexit [33][34][35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further research is needed to explore what these opportunities might be; however, some commentators have suggested that the Policy divergence enabled by Brexit may in fact benefit sectors of Industry (Gravey et al 2018). Culkin and Simmons (2019) feed into this debate, suggesting that innovation is not best fostered by a 'bonfire of regulation', rather by targeted financial support for innovation and growth in business.…”
Section: Opportunities Presented By Brexitmentioning
confidence: 99%
“…Finance is clearly a fundamental element for firms hungry and fit for growth. Culkin and Simmons (2019) cite the potential importance of the British Business Bank here. This organization is owned by the state with the aim of supporting business by increasing the flow of credit as well as by playing an advisory role.…”
Section: Support Neededmentioning
confidence: 99%
“…Although the UK has firms ripe for development in many areas of the economy, it does not necessarily have people with the right skill-sets that will be required to drive them forward. Culkin and Simmons (2019) point out there are needs here both in terms of skills training for workers but also the development of business skills for the people leading those companies.…”
Section: Support Neededmentioning
confidence: 99%
See 1 more Smart Citation